2022
DOI: 10.1021/acs.orglett.2c03813
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Catalyzed Late-Stage Introduction of Oxime Ethers into Peptides at the Carboxylic Acid Site

Abstract: We have developed a method of introducing biological oxime ether fragments into peptides by CuI-catalyzed latestage modification and functionalization of peptides, utilizing their acid moiety and varied 2H-azirines. As a result of its mild conditions, high atom economy, moderate yield, and excellent functional-group tolerance, the method can provide access to latestage peptide modification and functionalization at their acid sites both in the homogeneous phase and on resins in SPPS, providing a new tool kit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Isoxazoles with a heteroatom substituent at C5 have found wide application as convenient precursors of 2H-azirine-2-carboxylic acid derivatives, versatile building blocks for organic synthesis [31]. A very large number of structurally diverse azirines have been synthesized to date, including those which are of interest for biorthogonal chemistry [32], the chemistry of natural compounds [33], and medicine [34], but azirines with acridinyl substituents are still unknown in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Isoxazoles with a heteroatom substituent at C5 have found wide application as convenient precursors of 2H-azirine-2-carboxylic acid derivatives, versatile building blocks for organic synthesis [31]. A very large number of structurally diverse azirines have been synthesized to date, including those which are of interest for biorthogonal chemistry [32], the chemistry of natural compounds [33], and medicine [34], but azirines with acridinyl substituents are still unknown in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In this field, Sun et al [155] reported copper(I)-catalyzed vinyl nitrene-mediated late stage modification and functionalization of peptides through the reaction of N-alkoxylpeptidylamides and 2H-azirines (Scheme 99). N-alkoxylpeptidylamides can be pre-synthesized from amino acids and hydroxylamine.…”
Section: Ring-opening Of 2h-azirines To Acyclic Compoundsmentioning
confidence: 99%
“…In line with our ongoing interest in peptide chemistry, including those Trp modications, 33,39,42,[45][46][47][48][49] we have been trying to explore more mild, easy-to-manipulate alternatives for peptide modication/functionalization to enrich the scenario. Promoted by our previous work on organocatalytic indole functionalization 50,51 and Morita-Baylis-Hillman (MBH) carbonate based allylation, [52][53][54] and inspired by Chen's N-allylic alkylation of indoles with MBH carbonates, 55 we sought to explore the reaction between Trp and MBH carbonates to develop a novel strategy for peptide functionalization.…”
Section: Introductionmentioning
confidence: 99%